The impact of individual and contextual socioeconomic factors on colorectal cancer screening adherence in Turin, Italy: a multilevel analysis - Stefano Rousset; Elena Strippoli; Carlo Senore; Teresa Spadea; Marco Calcagno; Nicolás Zengarini; Gianluigi Ferrante (BMC Public Health)
Abstract Background Screening participation can be influenced by both individual socioeconomic position and contextual factors. In Italy, disparities exist regarding screening adherence, but it is important to understand the specific factors driving these disparities in specific locations according to different screening protocols. The aim of this study is to identify the impact of individual and contextual socio-economic factors on adherence to the organized colorectal cancer screening in the city of Turin, Italy. Methods Retrospective observational study on the population of assisted residents in Turin, eligible for colorectal screening from January 2010– June 2019. Colorectal screening in Piedmont involved inviting 58-year-old individuals to undergo a flexible sigmoidoscopy (FS) or, in case of non-adherence, a faecal immunochemical test (FIT). The program also included another protocol based directly on FIT as the first test. Adherence to the two screening protocols according to demographic/socioeconomic characteristics and contextual factors was evaluated with multilevel Poisson models. Results 90,227 eligible subjects (53% females) were analysed exploring adherence to FS/FIT. Lower likelihood of participation was found among males from High-Migratory-Pressure-Countries (HMPC), subjects with the lowest educational level, unemployed individuals, subjects living in rented houses, living alone/cohabiting and single parents. Among males, retirees and subjects living in more deprived areas participated more. 36,674 subjects (53% females) were analysed exploring adherence to the first FIT invitation. Adherence rate was higher among women (40% vs. 36%). Lower likelihood of participation was found among HMPC immigrants, males with the lowest educational level, people living in rented accommodation, living alone/cohabiting and single parents. Higher participation was found in retirees. In males, no differences were found between subjects living in more and less deprived areas, but a different likelihood of participation was observed across different areas of the city. Conclusions Socioeconomic and demographic characteristics influence access to organized colorectal screening in Turin. Immigrant status, low level of education, poor housing conditions and lack of social support, with some differences according to gender, emerged as the most significant barriers that should be tackled in order to increase screening participation and reduce inequalities. Contextual factors play a role only among male subjects.